Profil Hasil Ujian Nasional Materi Matematika SMP/MTs - Anggit Prabowo (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2018)
This study aims to describe the result of national examination in mathematics subject matter in junior high school start from 2013 to 2016. The method used was literature study by analyzing the report of national examination in junior high school start from 2013 to 2016 which published by Assessment Center of Research and Development Board, Ministry of Education and Culture. The result of this study shows that based on the result of national examination in junior high school start from 2013 to 2016, mathematics was the subject matter with the lowest in average score in three years last compared with three subject matters else (Indonesia Language, English Language, and Science). At that years, the average score of mathematics tended to decrease. Three dimensional, statistics, and probability were the most difficult to be understood by students of junior high school in Indonesia.